Reconsideration of the Epicanthus: Evolution of the Eyelid and the Devolutional Concept of Asian Blepharoplasty - Kwon, Bongsik; Nguyen, Anh H. (Seminars in Plastic Surgery, 2015)
Double eyelidplasty is the most frequent cosmetic procedure for Asians; however, the epicanthal fold has been a conundrum that has limited the cosmetic results of Asian blepharoplasty. To achieve satisfactory results in an Asian double eyelidplasty, the key is an understanding of the true nature of the epicanthus. We propose that the epicanthus developed in the eyelid's evolutionary process. Selective detachment and superomedial reposition of the preseptal portion of the upper orbicularis muscle can resolve the primary cause of epicanthal formation without functional impairment. The vertical skin shortage and resultant skin tension of the upper eyelid can be corrected by subcutaneous dissection and transverse advancement of skin flap. An epicanthoplasty is part of the core surgery for Asian double eyelidplasty, especially when forming a parallel type of double eyelid. Combined epicanthoplasty and double eyelidplasty need to be considered as one complete and inseparable procedure in surgery of the Asian eye.
Keywords: eyelid evolution; epicanthus; epicanthoplasty; double eyelid; double eyelidplasty; Asian blepharoplasty